Clinical Profile of Patients with Bilateral Optic Disc Swelling Attending in an Apex Eye Hospital in Bangladesh - Rahat, Ershadul H; Sarkar, Shayamal K; Hossain, Mujtahid M; Shimu, Farjana S; Mostafiz, Shafiul; Hossain, Farzana (Journal of National Institute of Ophthalmology, 2022)
Background: Patient with optic disc swelling demands thorough ophthalmic as well as systemic evaluation as it may reflect intraocular as well as systemic diseases. Early diagnosis and proper management of bilateral disc swelling is important, as it can save vision as well as life. This study is aimed to determine the socio-demographic and clinical profile of patients with bilateral optic disc swelling in a tertiary eye hospital of Bangladesh. Methods: This cross sectional study had been conducted over 102 patients with bilateral disc swelling at the Neuroophthalmology clinic of National institute of ophthalmology and Hospital, Dhaka between April 2019 and March 2020. Patients were selected purposively based on specific selection criteria. Detail history was taken, ocular examinations like visual acuity, color vision, field of vision, pupillary light reaction, fundus examination were done and relevant investigations included color fundus photograph, visual field analysis, Computed tomography scans and Magnetic Resonance Imaging were performed. All the information’s were recorded in a pre-designed data collection sheet. Results: The mean age of the patients was 30.2±10.8 years where 37.3% patients were from 18-27 year age group. Females (67.7%) were commonly presented with bilateral disc swelling than male (33.3%). Most of the patients commonly presented with the symptoms like headache (71.6%), dimness of vision (62.8%), nausea & vomiting (42.2%), ocular pain (21.6%) etc. Best corrected visual acuity of the study population was within 0-0.3 log MAR unit in the right eye in 55.9% cases and in the left eye in 59.8% cases. Majority of the patients (Right eye: 60.8%, Left eye: 63.7%) could read all plates while color vision assessment. About 20% patient had RAPD. About 17% patients had field defect in their right eyes whereas about 15% had visual filed defect in left eyes. Other than disc swelling, 14 patients had diplopia (13.7%), 12 patients had uveitis (11.8%). Out of 102 patients, 36 patients were clinically diagnosed as IIH (35.3%). Others were diagnosed as ICSOL (24.5%), bilateral optic neuritis (12.7%), VKH (12.7%), grade-IV hypertensive retinopathy (8.8%). The analysis of neuro imaging findings among the patients showed 72 patients (70.6%) had no space occupying lesions, 9 patients (8.8%) had meningioma, 6 patients had CP angle tumor (5.9%), 5 patients had empty sella (4.9%). Conclusions: Most of the Bangladeshi patients with bilateral disc swelling report to neuro-ophthalmology clinic in NIO&H are female and belong to 18-37 years age group. Among them headache is the most common presenting complaint and IIH is the most common clinical diagnosis. J. Natl. Inst. Ophthalmol. 2022;5(1):39-45